Functional ecology of calcrete aquifers in arid zone Western Australia - Saccò, Mattia (Curtin University, 2020)
This study investigates the ecology of an arid zone calcrete through an interdisciplinary design composed of multivariate analyses, hydrology, isotopic ecology and genetics. Our results indicate that the biotic community (microbes and stygofauna) is closely linked to the hydrodynamic conditions influenced by different rainfall regimes. The inflow of rainfall triggered shifts towards more deterministic dynamics, revealing a complex web of interactions. This investigation provides crucial untangling of the ecological dynamics regulating biotic communities in groundwaters.